Gene Expression Patterns of Osteopontin Isoforms and Integrins in Malignant Melanoma - Krisztina Jámbor; Krisztina Jámbor; Viktória Koroknai; Viktória Koroknai; Tímea Kiss; István Szász; István Szász; Péter Pikó; Péter Pikó; Margit Balázs; Margit Balázs (Pathology and Oncology Research, 2022)
Osteopontin (OPN) is a multifunctional glycoprotein that physiologically interacts with different types of integrins. It is considered to be a possible prognostic biomarker in certain tumor types; however, various splicing isoforms exist, which have not been investigated in melanoma. We aimed to define the relative expression pattern of five OPN isoforms and clarify the prognostic significance of the splice variants in melanoma. We also aimed to investigate the expression pattern of eight integrins in the same tumors. Gene expression analyses revealed that the relative expression of OPNa, OPNb, and OPNc is significantly higher in metastatic tumors compared to primary lesions (p < 0.01), whereas the expression of OPN4 and OPN5 was low in both. The more aggressive nodular melanomas had higher expression levels compared to the superficial spreading subtype (p ≤ 0.05). The relative expression of the eight tested integrins was low, with only the expression of ITGB3 being detectable in nodular melanoma (Medianlog2 = 1.274). A positive correlation was found between Breslow thickness and the expression of OPNc variant, whereby thicker tumors (>4 mm) had significantly higher expression (p ≤ 0.05). The Breslow thickness was negatively correlated with the expression of OPN4, and similarly with ITGA2. OPNc also exhibited significant positive correlation with the presence of metastasis. Our data show that high expression of OPNa, OPNb, and especially OPNc and low expression of OPN4 and ITGA2 are associated with an advanced stage of tumor progression and poor prognosis in melanoma.